INFLUENCE OF COMPLEX EFFECT ON MECHANICAL PROPERTIES OF POLYMERIC FILMS - Voronova, N. A.; Drobyshev, A. S.; Kupchishin, A. I.; Muradov, A. D.; Taipova, B. G. (Recent Contributions to Physics, 2009)
The research of influence of complex effect of different kinds on polymeric films’ mechanical properties. Determined that complex effect of temperature, static load and radiation on tedlar films for unirradiated sample and with radiation doses of 25, 50 kHz during first 10 seconds there is a sharp growth of relative elongation, then ε changes on the basis of lineal law up to it’s rupture. In the samples radiated with doses of 100 kHz to 1 MHz growth of relative elongation takes place in first 1-3 seconds and is 91.2% for radiated with D = 250 kHz and 74.8% for radiated with D = 1 MHz. With increasing of radiation dose time from load application to sample’s rupture decreases: unirradiated film under complex effect of temperature and static load has a time of rupture of 274 sec., and for radiated samples D = 1 MHz the time is equal to 94 sec., that is the rupture of main chain is three times faster. Developed a catastrophic model of polymer materials destruction on the basis of experimental research of their physical-mechanical properties.